Utilizing non-histological serological markers in the prediction of recurrence and metastasis in head and neck melanoma - L. O. Kovtun (Journal of Ophthalmology, 2024)
There is a need for the development of additional prognostic melanoma (e.g., head and neck melanoma) biomarkers to stratify melanoma patients and reliably identify high-risk subgroups with the aim of providing effective personalized therapy.